Esporotricose óssea em gato causada por Sporothrix brasiliensis - Franceschi, Natália Tomazi; Spanamberg, Andréia; Dhein, Juliana de Oliveira; Bazotti, Maiara Scapini; Rvazzolo, Ana Paula; da Silva, Isabel Tomazi; da Costa, Fernanda Vieira Amorim; Ferreiro, Laerte (Acta Scientiae Veterinariae, 2017)
Background: Sporotrichosis is a deep cutaneous mycosis caused by the Sporothrix species complex, dimorphic fungi of which at least five are of clinical importance: S. brasiliensis, S. globosa, S. luriei, S. mexicana, and S. schenckii sensu stricto. The disease affects humans and animals, especially cats, which can manifest a wide spectrum of clinical sings, from cutaneous-lymphatic involvement to disseminated form. Infection usually results from direct inoculation of the fungus into skin. Zoonotic transmission is associated with scratching or biting of sick cats. The aim of this work was to report an atypical case of bone sporotrichosis in a cat. Case: A 5-year-old, male, neutered, mongrel and indoor cat was present at the Veterinary Clinic Hospital, Federal University of Rio Grande do Sul (HCV-UFRGS), Porto Alegre, Brazil, with lameness and increased volume in the left hindlimb. The animal had been treated intermittently with itraconazole during the last three years due to another cutaneous lesion which was recurrent and undiagnosed. A firm and painful mass was found in tarsal region of left hindlimb, that had approximately 5 cm in diameter. Radiographic examination of the left tibial-tarsal joint revealed bone lysis in the fifth metatarsal calcaneus, in addition to periosteum proliferation in calcaneus, tibio-tarsal subluxation, presence of osteophytes in tarsal bones and increase in soft tissue volume. Histopathological analysis of the biopsied tissue showed piogranulomatous inflammation. No yeast-like structures were observed in cytopathological exam. Tissue fragments were plated and Sporothrix sp. complex growth in mycological culture (Sabouraud Cycloheximide Chloramphenicol Agar). Physiological tests (growth rate at different temperatures and assimilation of sucrose and raffinose) were conducted for the differentiation of the species of complex. Molecular identification was performed using panfungal primers (ITS3-F / ITS4-R). The diagnosis of bone sporotrichosis caused by Sporothrix brasiliensis was based on clinical signs, mycological (confirmed by isolation and identification in culture medium) and molecular methods. Treatment was based on excision of the limb associated with oral administration of itraconazole and silymarin for two months. Unfortunately, three months later new nodules were seen at the abdomen and biopsy samples were positive in a new fungal culture for Sporothrix sp. Oral treatment was then restarted for four months. The cat is now free of lesions for six months and clinical monitoring visit is usually done once per month. Discussion: Sporotrichosis is a fungal infection with worldwide distribution, mostly in tropical and subtropical countries, characterized by cutaneous and subcutaneous lesions with regional lymphocutaneous dissemination, but some pulmonary and systemic infections in human have been reported. Cats are frequently infected with sporotrichosis in Brazil and develop a scattered cutaneous condition. On the other hand, the systemic form of the disease have been more observed with a disseminated respiratory or systemic condition, including infection of the lungs, liver, spleen, kidney, testis, eyes, bones, central nervous system, gastrointestinal tract, and mammary glands may also be affected. The occurrence of bone sporotrichosis, without skin lesions, show the high susceptibility of these animals to infection by Sporothrix. Molecular methods for the differentiation of Sporothrix complex are needed when the conventional methodology (histopathology and culture) does not allow the identification of the agent. The reference standard for diagnosing sporotrichosis is microscopic characterization of the pathogen isolated in culture. In our study, although the culture was positive, PCR was necessary for detecting and identifying Sporothrix brasiliensis. The reported case of bone sporotrichosis emphasizes the importance of a conclusive and differential diagnosis in feline lytic bone lesions based on the detection of fungal in the tissue by molecular methods associated with the isolation of the agent in a fungal culture.